Study of the anti-inflammatory, analgesic, ulcerogenic and anti-ulcerogenic activity of N-isopropenylimidazole zinc complex derivative - Pavel A. Galenko-Yaroshevsky; Olga V. Shelemekh; Viktor L. Popkov; Andrey V. Zadorozhniy; Irina B. Nektarevskaya; Natalia D. Bunyatyan; Roman A. Murashko; Svetlana A. Lebedeva; Anait V. Zelenskaya; Aleksandr V. Uvarov; Olga N. Gulevskaya; Lusine O. Alukhanyan; et al. (Belgorod National Research University, 2024)
Introduction: Although nonsteroidal anti-inflammatory drugs (NSAIDs) have a clear therapeutic benefit, they can also have serious side effects. The most serious of these is the ulcerogenic effect, which can result in a decline in the quality of life or even death. This calls for the search for and creation of novel compounds with potent anti-inflammatory properties that do not have adverse effects on the digestive system. The aim of the study was to investigate the anti-inflammatory, analgesic, ulcerogenic and anti-ulcerogenic activities of N-isopropenylimidazole zinc complex derivative. Materials and Methods: Experiments in rats and mice were used to determine the median lethal dose LD50 for N-isopropenylimidazole zinc complex derivative (laboratory name Pilim-1). Experimental models of acute exudative inflammation and chronic proliferative inflammation were used. In the first case, the inflammation was induced by sub-plantar injection of carrageenan and a complete Freund's adjuvant into the hind paw of rats. In the second case, the inflammation was induced by the implantation of a sterile cotton pellet ("cotton pellet-induced granuloma") under the skin of rats. Acute and tonic pain, visceral, and somatic deep pain were simulated using the formalin test in rats and the acetic acid-induced writhing test in mice, respectively. The ulcerogenic and anti-ulcerogenic effects of Pilim-1 were studied in rat experiments. Pilim-1 and the reference drugs diclofenac, indomethacin and famotidine were administered intragastrically. Results and Discussion: Pilim-1 showed marked anti-inflammatory and analgesic effects, demonstrated less toxicity than diclofenac and indomethacin, while its activity is comparable to diclofenac and superior to indomethacin. Its therapeutic index is higher than that of indomethacin and diclofenac and, in contrast, it essentially has no ulcerogenic effect and exhibits stronger anti-ulcerogenic activity than famotidine. It appears that the anti-inflammatory, analgesic, and gastroprotective properties of Pilim-1 are largely due to its antioxidant and antihypoxic properties, its inhibitory effects on cyclooxygenase and 5-lipoxygenase, and the presence of imidazole and zinc in its structure, both of which have a wide range of biological activity. Conclusion: Pilim-1 can be recommended for further preclinical studies due to its relatively low (practically absent) ulcerative activity, strong anti-inflammatory, analgesic, and anti-ulcerative effects, greater therapeutic index, and less acute toxicity in comparison with diclofenac and indomethacin.